Valvular heart disease in pregnancy. (11th January 2023) - Timmons, Paul; Partridge, Gemma; McKelvey, Alastair; Lyall, Hamish; Morosan, Monica; Freeman, Leisa
Abstract : Key content: Pregnancy‐induced changes in haemodynamic physiology can place considerable strain on cardiac function in some women with valvular disease. Regurgitant valve lesions are usually better tolerated in pregnancy than stenotic lesions, although the risk of obstetric complications is increased in both. Pre‐conception counselling is essential for all women with valvular disease. Optimising anticoagulation is a particular challenge in women with mechanical valves. Learning objectives: To understand the World Health Organization (WHO) classification of maternal cardiac disease and how this affects counselling regarding decisions around pregnancy for women with valve pathology. To understand how valve disease affects pregnancy and vice versa. To gain insight into the anaesthetic and haematological considerations for managing women with valvular disease. Ethical issues: What is the optimum anticoagulation regimen for women with mechanical heart valves in pregnancy that balances both maternal and fetal risks?